Asymptotic and Dynamical Analyses of Heat Transfer through a Rectangular Longitudinal Fin - C. Harley (Journal of Applied Mathematics)
The steady heat transfer through a rectangular longitudinal fin is studied. The thermal conductivity and heat transfer coefficient are assumed to be temperature dependent making the resulting ordinary differential equation (ODE) highly nonlinear. An asymptotic solution is used as a means of understanding the relationship between key parameters. A dynamical analysis is also employed for the same purpose.